2016
DOI: 10.1016/j.molcel.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Regions of Cytosine Methylation and H3K27 Acetylation Suggest an Active Role for DNA Methylation at Enhancers

Abstract: Summary The role of cytosine methylation in the structure and function of enhancers is not well understood. In this study, we investigate the role of DNA methylation at enhancers by comparing the epigenomes of the HCT116 cell line and its highly demethylated derivative, DKO1. Unlike promoters, a portion of regular and “super-” or “stretch” enhancers show active H3K27ac marks co-existing with extensive DNA methylation, demonstrating the unexpected presence of “bivalent chromatin” in both cultured and uncultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 50 publications
7
81
0
Order By: Relevance
“…A previous study (39) found that loss of KDM5B in mouse embryonic stem cells (mESC’s) resulted in a misregulation of H3K4me3 and a subsequent decrease in H3K27ac at enhancers, implying a loss of activity. Furthermore, DAC has recently been suggested to have an antagonistic effect on super-enhancer activity in a number of cancer cell lines, though the effect at regular enhancers remains unclear (40). We analyzed H3K4me3 and H3K27ac localization at candidate enhancers (as identified by ChromHMM) in MCF-7 via ChIP-seq (32,41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study (39) found that loss of KDM5B in mouse embryonic stem cells (mESC’s) resulted in a misregulation of H3K4me3 and a subsequent decrease in H3K27ac at enhancers, implying a loss of activity. Furthermore, DAC has recently been suggested to have an antagonistic effect on super-enhancer activity in a number of cancer cell lines, though the effect at regular enhancers remains unclear (40). We analyzed H3K4me3 and H3K27ac localization at candidate enhancers (as identified by ChromHMM) in MCF-7 via ChIP-seq (32,41).…”
Section: Resultsmentioning
confidence: 99%
“…2E), although epistatic pathway interactions likely contribute to this observation as well. To our knowledge, only one study regarding the role of DAC at distal regulatory elements has been published (40). The authors found that DNMT inhibition led to decreased activity of super-enhancers in MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancers are known as tissue-specific regulators of gene expression during cell differentiation and cancer development (33, 38, 40, 41). Enhancers are commonly identified as genomic elements enriched by histone modification (H3K27ac and different H3K4me isoforms), predominantly hypomethylated (42, 43), and occupied by various transcription factors, BRD4 (BET bromodomain protein, an activator of RNA polymerase II - PolII), MED1 (PolII transcription subunit) proteins, and PolII itself (33). H3K27ac enrichment at enhancer regions is recognized by BRD4, whose inhibition leads to a dysregulation in gene expression of oncogenes such as MYC, MYB, MMP9, BCL2, and CCND1 (40, 41, 44, 45).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation also occurs at actively transcribed gene bodies and at active enhancers (Baubec et al, 2015; Charlet et al, 2016; Dhayalan et al, 2010; Rinaldi et al, 2016). DNMTs are responsible for catalysing the transfer of a methyl group to DNA.…”
Section: Metabolism-driven Epigenetic Alterations In Cancermentioning
confidence: 99%